Insights on comprehensive characterization of distinct growth stages of Sterculia foetida pod as a potential feedstock for bioethanol production - Pasupathi, Saroja; Rahman, Sameeha Syed Abdul; Karuppiah, Sugumaran (Scientific reports, 2025)
Lignocellulosic biomass explores a sustainable and renewable energy source that could provide a suitable solution to energy demands. However, diversity is the main obstacle that hinders the biorefinery approach to bioethanol production. In this study, the non-edible feedstock, S terculia foetida pod, green-colored skin (GSFP), and brown-colored skin (BSFP) were used as feedstock for the production of bioethanol. To examine the comprehensive characterization of selected biomass, namely BSFP and GSFP, the various methods, namely physicochemical analysis, proximate analysis, ultimate (CHNS) analysis, bulk density, and calorific value were employed. The functional group analysis, thermal stability, surface morphology, and crystallinity index for biomasses were characterized by FTIR spectroscopy, Thermo-gravimetric (TGA) analysis, scanning electron microscope (SEM), and XRD analysis. The elemental and chemical composition of GSFP and BSFP were extensively evaluated using different methods. The value-added precursors, namely cellulose and lignin isolated from GSFP and BSFP. The cellulose content in GSFP and BSFP pods was found to be 35.28 ± 3.39% and 33.95 ± 4.49% and the lignin content was 17.37 ± 3.54% and 20.79 ± 8.78% respectively. The obtained cellulose from GSFP and BSFP was subjected to two-step acid hydrolysis on different SL ratio (1:10–5:10) to prepare fermentable sugars at different concentration (g/L). Based on the different sugar concentration, the bioethanol concentration (0.91 to 18.78 g/L; 0.23 to 12.23 g/L) and specific bioethanol yield (0.44 to 1.52 g/g; 0.13 to 1.55 g/g) increased for both BSFP and GSFP respectively.